Reforming at the Subnational Level : Global Experiences - World Bank (World Bank, Washington, DC, 2021)
Reforming the business regulatory framework requires overcoming many hurdles, especially in federal countries. At the same time, global experience shows that a higher degree of decentralization is not associated with fewer business regulatory reforms. This policy note presents strategies to promote investment climate reforms across all levels of government in federal, state, and municipal. In most countries, policy making is split between : (i) the central government, which oversees foreign relations and the domestic rule of law; and (ii) local governments, which manage municipal and rural affairs. In federal countries, subnational governments (SNGs) also possess legislative powers that empower them to pass, enforce, and interpret laws. The focus in this note is to learn from the successful practices and strategies used to align federal and SNG reform incentives. The first section of the note provides an overview of power-sharing structures and the critical challenges encountered. The second part of the note focuses on consensus-building strategies, and the third part describes several successfully leveraged incentive strategies.